Validasi Instrumen Indeks Kota Berkelanjutan dengan Analisis Faktor - Yasid Saleh; Mohamad Khairul Anuar Ghazali; Hanifah Mahat; Mohmadisa Hashim; Nasir Nayan; Suhendro Suhendro (Jurnal Wilayah dan Lingkungan, 2022)
Creating sustainable cities and communities is one of the key goals in the Sustainable Development Agenda by 2030. To implement this goal, a measurement instrument needs to be developed to assess the extent of sustainability of each city, including heritage cities. Therefore, this study aims to validate the heritage city sustainability index instrument in Malaysia using exploratory factor analysis (EFA) and confirmation factor analysis (CFA) methods. The survey form was distributed to 1000 respondents living in 10 heritage cities throughout Malaysia using a simple random sampling technique. For the purpose of item identification and grouping, EFA and CFA analysis were used. The results of the study have formed and accepted five main constructs of heritage city sustainability in Malaysia namely Economic Prosperity (13 items), Social Well -Being (9 items), Environmental Well -Being (8 items), Heritage Culture (9 items) and The Role of Government and Community (18 items). All items in each construct achieved a good Cronbach Alpha value of above 0.70 and met the normality test requirements. The index value conditions set by Kaiser-Meyer-Olkin (KMO) and Bartlett’s Test of Sphericity in this study also showed satisfactory values. The formation of the five constructs of this study directly demonstrates the connectivity and appropriateness between items according to constructs. The instrument, which has been certified using EFA and CFA techniques, will assist in measuring the level of sustainability of heritage cities in Malaysia.